2019
DOI: 10.1142/s0217984920500098
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solutions of some integral fractional differential–difference equations

Abstract: The invariant subspace method (ISM) is a powerful tool for investigating analytical solutions to fractional differential–difference equations (FDDEs). Based on previous work by other people, we apply the ISM to the space-time fractional differential and difference equations, including the cases of the scalar space-time FDDEs and the multi-coupled space-time FDDEs. As a result, we obtain some new analytical solutions to the well-known scalar space-time Lotka–Volterra equation, the space-time fractional generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…So, it is expected that the fractional logistic equation will give a more suitable description for the population growth. Other fractional models, including the generalized time-fractional diffusion equation, quadratic integro-differential equations, integral fractional differential–difference equations, fractional stochastic heat equation, fractional integro-partial differential equations, and fractional-order HIV/AIDS model, can be found in [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…So, it is expected that the fractional logistic equation will give a more suitable description for the population growth. Other fractional models, including the generalized time-fractional diffusion equation, quadratic integro-differential equations, integral fractional differential–difference equations, fractional stochastic heat equation, fractional integro-partial differential equations, and fractional-order HIV/AIDS model, can be found in [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous research [21], Asaduzzman et al, have studied the special cases of Equation (1) by considering α = 2. In this paper, we have extracted the general solutions of MAE according to α as being in the solutions of Equations (16), (18), and (32). Moreover, we have also investigated other values of α such as complex and rations in the coefficients of Equations (19), (21), (23), (25) and (29).…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…More general properties of auxiliary and sub-equation function methods have been comprehensively introduced in the literature [28,29]. Moreover, there are many published methods for solving similar equations using different techniques and methods [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, we feel motivated to carry out the rigorous study of this pandemic from fractional variant. This is because, it can be noted that, in the recent past, multifarious scientists have shown that the fractional calculus can more precisely explain natural phenomena than the integer calculus 8‐28 . In light of this fact, the noninteger calculus becomes increasingly significant and common in the realistic cases modeling, those with memory effects in particular.…”
Section: Introductionmentioning
confidence: 99%